Current Knowledge on Selenium Biofortification to Improve the Nutraceutical Profile of Food: A Comprehensive Review - D'Amato, Roberto (2020)
Selenium (Se) is an important micronutrient for living organisms, since it is involved in several physiological and metabolic processes. Se intake in humans is often low and very seldom excessive, and its bioavailability depends also on its chemical form, with organic Se as the most available after ingestion. The main dietary source of Se for humans is represented by plants, since many species are able to metabolize and accumulate organic Se in edible parts to be consumed directly (leaves, flowers, fruits, seeds, and sprouts) or after processing (oil, wine, etc.). Countless studies have recently investigated the Se biofortification of plants to produce Se-enriched foods and elicit the production of secondary metabolites, which may benefit human health when incorporated into the diet. Moreover, feeding animals Se-rich diets may provide Se-enriched meat. This work reviews the most recent literature on the nutraceutical profile of Se-enriched foods from plant and animal sources.